The necessary murder of Nonie Blake - Shames, Terry (Shames, Terry. Samuel Craddock mystery., 2016)
"Nonie Blake is back home from a mental institution where she has spent the last twenty years, and people in Jarrett Creek are worried. Maybe too worried, for within a week of her return, Nonie is murdered. Chief Samuel Craddock thinks the only possible suspects are members of her tight-lipped family. Ever since Nonie tried to kill her sister when she was fourteen and was sent away to the institution, the family has kept to itself. Clues are scarce and Craddock is stumped. So he checks with therapists at the mental hospital to see whether they can add anything useful to his investigation. But he discovers that she has not been there for ten years. Now Craddock has to find out where Nonie has been all this time. Soon Craddock finds himself dealing not only with murder, but layers of deception and secrets, and in the midst of it all a new deputy, one Maria Trevino, sent by the sheriff to beef up security in the small Texas town"--